Proteomic characterization of the multiple forms of the PLAs from the venom of the social wasp Polybia paulista - dos Santos, Lucilene Delazari [UNESP]; da Silva Menegasso, Anally Ribeiro [UNESP]; Aparecido dos Santos Pinto, Jose Roberto [UNESP]; Santos, Keity Souza; Castro, Fabio Morato; Kalil, Jorge Elias; Palma, Mario Sergio [UNESP] (Wiley-Blackwell, 2011)
The phospholipases A(1) (PLA(1)s) from the venom of the social wasp Polybia paulista occur as a mixture of different molecular forms. To characterize the molecular origin of these structural differences, an experimental strategy was planned combining the isolation of the pool of PLAs from the wasp venom with proteomic approaches by using 2-D, MALDI-TOF-TOF MS and classical protocols of protein chemistry, which included N- and C-terminal sequencing. The existence of an intact form of PLA(1) and seven truncated forms was identified, apparently originating from controlled proteolysis of the intact protein; in addition to this, four of these truncated forms also presented carbohydrates attached to their molecules. Some of these forms are immunoreactive to specific-IgE, while others are not. These observations permit to raise the hypothesis that naturally occurring proteolysis of PLA(1), combined with protein glycosylation may create a series of different molecular forms of these proteins, with different levels of allergenicity. Two forms of PLA(2)s, apparently related to each other, were also identified; however, it was not possible to determine the molecular origin of the differences between both forms, except that one of them was glycosylated. None of these forms were immunoreactive to human specific IgE.
Keywords: Animal proteomics; Immunoreactivity; Phospholipase A(1); PTM; Wasp venom